TINDAKAN PLAGIASI DI KALANGAN MAHASISWA FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS RIAU - Serafina K. Simbolon; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT The act of plagiarism is very contrary to grades and academics. But in their academic activities, students sometimes do things that are dishonest or cheating, namely plagiarism in completing tasks given by lecturers. Therefore, this study aims to find out how plagiarism acts among students of the Faculty of Social and Political Sciences, University of Riau. This study used purposive sampling method with 125 respondents. The results showed that the plagiarism actions most often done by students were (1) Changing the arrangement of other people's works without including sources with a percentage of 66,4%, (2) Combining several papers but only including one source with a percentage of 63.2%, (3) copying the entire writing of an essay without including the source with a percentage of 62,4%. Meanwhile, the biggest factor that causes plagiarism is laziness with a percentage of 89,6%. This study provides information that most students know that they have committed plagiarism but still do it, but there are also some students who do plagiarism because of lack of knowledge in recording sources. Keywords: Students, Plagiarism